PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS SISWA : PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS SISWA (Studi Kasus Siswa Kelas XI Madrasah Aliyah Al-Hikam Jatirejo Diwek Jombang) - zulfa; umam, khoirul (PAI FAI UNHASY Tebuireng Jombang, 2025)
Abstract: This examination looks at the use of a task based learning model to build the imagination of class XI understudies at Madrasah Aliyah Al-Hikam Jatirejo Diwek Jombang. A learning model is a plan or model that is utilized as a device in coordinating learning in the home so that the learning targets that will be passed on to understudies can be accomplished well and in an efficient way. In its acknowledgments, there are different kinds of learning models, one of which is the effort based learning model. Hence, executing an endeavor based learning model can build understudies' creative mind. One of the points of this examination is to apply an undertaking based learning model. These specialists utilized a contextual investigation based subjective methodology for this exploration. This methodology utilizes interviews, insight and documentation strategies. The consequences of the exploration examined are 1) The effort based learning model is a learning plan that spotlights on understudies where understudies move powerfully while teaching and learning practices that are given over by instructors by making the undertaking an issue that should be reviewed. 2) to build understudies' innovativeness, another learning model is required that they have never known. So understudies will feel inquisitive to follow each step towards an instructive encounter. 3) Execution of a learning model in view of tasks that understudies get ready prior to being carried out in class, with project tasks that are changed at each gathering. The appraisal stage begins from coordinating understudy efforts to presenting project results.